Effect of ZnO-NPs Enhanced Vermicompost (NEV) on the Growth, Leaf Nutrient Content, Yield, and Tomato’s Quality (Solanum lycopersicum) - Nurhidayati, Nurhidayati; Qur’ania, Anita; Widowati; Ansari, Abu Saad (PLANTA TROPIKA, 2026)
Zinc oxide nanoparticles (ZnO-NPs) can be used as nanofertilizers and nanogrowth regulators to enhance plant agronomic performance. Nevertheless, far too little interest has been paid to the impacts of ZnO-NPs integrated with vermicompost in horticultural crop cultivation. This study investigated the effects of ZnO-NP-enhanced vermicompost (NEV) on the growth, leaf nutrient content, yield, and quality of tomato plants. A controlled greenhouse experiment was conducted, in which tomato plants were subjected to various treatments, including application of NEV combined with various doses of ZnO-NPs via direct soil and foliar spray, compared with control, NPK fertilizer, and vermicompost. The results showed that direct soil application of NEV positively affected tomato leaf growth and NPK content. This enhanced nutrient uptake contributed to increased tomato yield. The direct soil application of NEV (ZnO 50 mg kg-1) increased the tomato fruits (315% and 183%) and the fresh weight of tomato fruits (344% and 197%) in comparison to the control and NPK fertilizer. Additionally, the study demonstrated that applying NEV not only increased yield but also increased the vitamin C content of tomatoes. The findings highlight the potential of this innovative agricultural approach as a sustainable means to enhance tomato production.